Aldosterone/Direct Renin Concentration Ratio Versus Aldosterone/Plasma Renin Activity for Diagnosis of Primary Hyperaldosteronism: Case Presentation - Shanik, Michael Howard (J Endocr Soc, 2021)
Aldosterone/Direct Renin concentration ratio versus Aldosterone/Plasma renin activity for diagnosis of Primary Hyperaldosteronism: Case presentation. Introduction: Primary hyperaldosteronism (PA) is the most common cause of secondary hypertension. Endocrine Society guidelines recommend using aldosterone-to-renin ratio (ARR) for screening of PA(1). This ratio can be obtained using two different methods. The first is plasma aldosterone concentration (PAC) divided by plasma renin activity. ARR greater than 20 is suggestive of PA. Further testing is required for confirmation. Due to limitations and challenges in obtaining PRA, another method of measurement was developed in which the direct renin concentration (DRC) is measured. There have been inconsistent recommendations regarding what ratio is appropriate using this assay to diagnose hyperaldosteronism. The aim of this case presentation is to review a patient with PA in whom both measurement methods were used and compared for screening. Case Presentation: A 45-year woman with past medical history of Graves’ disease and hypertension presented with hypokalemia. Blood pressure was well-controlled on amlodopine for 3 years. PAC and DRC were measured. PAC was 21.2 ng/dL and DRC 2.8 pg/ml with ARR 7.6. This was repeated and confirmed (PAC 19.6 ng/dL and DRC 3.9 pg/ml with ARR 5). Plasma Renin Activity (PRA) was measured. PAC was 36.3 ng/dL and PRA was 0.19 ng/ml/hr (ARR 191), suggestive of hyperaldosteronism. Further workup including a CT scan of the abdomen with IV and oral contrast demonstrated an enhancing 1.8 cm nodule in the left adrenal gland. Adrenal vein sampling was performed. Left adrenal vein aldosterone level was 1400 ng/dl and on the right, 33.1 ng/dl. The patient was treated with left laparoscopic adrenalectomy. The pathological evaluation of the specimen demonstrated a 2.5 cm adenoma of benign etiology. Later follow-up showed the patient was normokalemic with PAC of 3.1. Conclusion: Patients with PA despite controlled hypertension, experience higher rates of cardiovascular events, hence early and accurate diagnosis is essential. PRA measurement has multiple limitations including inter-laboratory variations, higher cost, availability in only advanced laboratories and values influenced by blood pressure medications. Therefore, some institutions have replaced it with direct renin concentration (DRC) which is cheaper and more widely available. DRC has limitations with fewer positive ARR results. When the clinical suspicion is high, PRA is the more precise study to calculate ARR. The Management of Primary Aldosteronism: Case Detection, Diagnosis, and Treatment: An Endocrine Society Clinical Practice Guideline. John W. Funder, Robert M. Carey, Franco Mantero, et al. The Journal of Clinical Endocrinology & Metabolism, Volume 101, Issue 5, 1 May 2016, Pages 1889–1916, https://doi.org/10.1210/jc.2015–4061.